Contextualization of hiv Prevention Initiatives in Sub-Saharan Africa, with Special Reference to Gender Issues in Contexts of Human Dislocation and Migration - Stewart, Gordon J. (Mission studies, 2014)
The subject of hiv/aids prevention in public discourse in sub-Saharan Africa is often focused, and not without good reason, on modification of sexual behavior, exemplified in the well-known abc strategy – Abstain, Be faithful, wear a Condom. It is here suggested that this narrowing of focus onto sexuality, in contexts where traditionally public discourse on the subject is taboo, could result unhelpfully in significant stereotyping and stigmatization of People Living with hiv & aids, especially women. Furthermore, other factors which serve as potential “drivers” of the epidemics are often omitted from prevention initiatives. These include etiologies of sickness especially as they relate to hiv infection, socio-cultural and economic factors, as well as religious and theological perspectives. These have potential impact on both men and women, but in many instances have even more serious consequences for girls and women. Considering the conditions of people subject to displacement within or forced migration from their countries, the negative impacts of these “drivers” of the epidemics are enhanced even further. Women in particular are most vulnerable to abuse and victimization. In this light, it is recommended that a more nuanced and more contextualized understanding of the epidemics be pursued, one which does not overlook biomedically important issues (including sexuality) but addresses a range of other negative perspectives and practices which result in stigmatization and victimization of women and girls, increasing their vulnerability to abuse and consequently of hiv infection. In focusing on hiv prevention in terms of gender inequities in sub-Saharan society in general and among internally displaced and forced migrant populations in particular, it is important to identify missiological insights that have significance for the missional challenges.